A case study about Copyright Law awareness and infringement among office management students in UiTM Shah Alam / Mohammed Rasul Oon - Oon, Mohammed Rasul (2002)
Copyright law had been established a long time ago and as the law that protect intellectual properties, the Copyright law is mostly one of the law that are very important but it always been forgotten by majority of people. This is because the copyright law is less practice and uphold in our country. The lack of enforcement ofthis copyright law make the user infringe the copyright law whenever they want to. This study explores the awareness and infringement of the copyright law in UiTM Shah Alam and to be more specific , the study will be over Faculty of Office management. The most important objective ofthis study to find out the solutions to this infringement problem and to determine the factors that caused the copyright infringement. In order to get the relevant data, the researcher used the method of questionnaires which will give the students himself or herself to respond to the situation.